A marginalização da profissional criativa na conquista de posições nas áreas de planejamento e criação no setor de Publicidade e Propaganda no eixo Rio/São Paulo - Nóbrega, Ana Carolina Soares de (2020)
The aim of the research is to analyse the marginalization of the creative professional in winning and maintaining positions in the areas of planning and creation in the sector of Advertising in the Rio-São Paulo axis from the period 2015 to 2020. The central argument is, in contrast to the supposedly inclusive environment of the creative economy, the marginalization of the creative professional in the Advertising and Propaganda sector on the Rio-São Paulo axis, between 2015 and 2020, is the result of maintaining a patriarchal culture, a means by which Brazilian society organizes itself and establishes the superiority of men when reproducing different gender hierarchies and not creating equal opportunities for men and women, which widens the gap between them by reinforcing the idea that women would be a more sociable being and that in some way ends up reiterating this type stereotype that puts it on a subordinate plane with regard to activities that employ the creativity of the professional. To this end, the methodology was based on bibliographic research and semi-structured in-depth interviews. The bibliographic review that addresses gender issues and women in Brazilian society is based on the works of Judith Butler (2003), Céli Regina Jardim Pinto (2003), Ilze Zirbel (2007), Kergoat (2009), Marcia Tiburi (2019) , Jacilene Maria Silva (2019), the social perspective of Corporate Social Responsibility was based on the work of Perista et al. (2008) and Positive Design used the study by Desmet and Pohlmeyer (2013).The work made it possible to verify that there is a marginalization of women in the sector of Advertising and Propaganda that is reiterated by gender stereotypes widely spread in Brazilian society that maintains a patriarchal culture. In this way, the general lines of a potential course that would come to allow the overcoming of these standards are suggested